Performing Arts, Public Policies, and Social Representations. Theater as a Tool for Building Civic Culture - Mesa González, María Isabel; Murillo Carvajal, Felipe (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
At the subnational level, various public administrations have adopted a civic culture approach as a management tool to encourage desirable behaviors and discourage those that generate collective problems. This study asks: how do social representations around theater influence the construction of civic culture in Medellín? The objective is to identify these representations and analyze the role of theater as a public policy resource in the San Ignacio District. A qualitative-ethnographic design was employed, combining participant observation in local theaters and semi-structured interviews with spectators aged 25 to 35, complemented with indicators from the Civic Culture and Citizen Perception Surveys. The findings show that theater attendance fosters values such as diversity, respect, and empathy, which reinforce social norms and coexistence. Thus, theater emerges as a public policy tool with the capacity to promote prosocial behaviors and contribute to the consolidation of civic culture.